Optimization method for reducing power consumption of prebaked anode and improving viscosity of modified asphalt
By optimizing the asphalt modification process, reducing the roasting temperature, optimizing the molding process and recycling waste asphalt, the problems of insufficient asphalt bonding performance, high production energy consumption, unstable anode quality, environmental protection and waste in traditional prebaked anode production are solved, and the effects of reducing electricity consumption, improving bonding performance and reducing environmental pollution are achieved.
Patent Information
- Application Number
- CN202510120016.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-25
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During the production process of traditional prebaked anode, there are problems of insufficient asphalt bonding performance, high production energy consumption, unstable anode quality, and environmental protection and resource waste.
By optimizing the asphalt modification process, catalytic modification technology and nanomaterial addition, reducing the calcination temperature and adopting segmented heating method; optimizing the forming process, high-pressure forming technology; and recycling waste asphalt to improve the performance of regenerated asphalt through regeneration technology.
It significantly reduces the electricity consumption in the production process of pre-baked anode, improves the bonding performance of modified asphalt, enhances the strength and service life of the anode, and reduces resource waste and environmental pollution.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of prebaked anode manufacturing technology for aluminum electrolysis, and specifically to an optimization method for reducing the power consumption of prebaked anodes and improving the adhesion of modified asphalt. Background Art
[0002] Prebaked anodes are indispensable consumable materials in the aluminum electrolysis production process. Their quality directly affects the efficiency, energy consumption and quality of aluminum electrolytic cells. Prebaked anodes are mainly made of raw materials such as petroleum coke and asphalt through molding and roasting processes. Among them, asphalt is used as a binder, and its performance plays a vital role in the strength, oxidation resistance and conductivity of the anode.
[0003] In the traditional production process of prebaked anodes, there are the following problems: insufficient asphalt bonding performance. Asphalt is used as a binder, and its bonding performance directly affects the mechanical strength and antioxidant properties of the anode. Traditional asphalt has a low softening point and insufficient bonding force, which leads to cracks and powdering of the anode during high-temperature electrolysis, affecting the stability of aluminum electrolysis production and the service life of the anode. The production energy consumption is high. In the production process of prebaked anodes, baking is a key link. The traditional baking process usually adopts a high-temperature rapid heating method. The baking temperature is generally above 1200°C, and the heating rate is fast. Although this high-temperature rapid baking process can ensure the sintering quality of the anode, it has high energy consumption, resulting in high production costs; the anode quality is not good. Stability. Due to the insufficient adhesion of asphalt and the unqualified roasting process, the quality of prebaked anodes is often difficult to guarantee. Key indicators such as density, strength, and conductivity of the anode are prone to fluctuations, resulting in reduced current efficiency and increased energy consumption during aluminum electrolysis production, and even affecting the quality of aluminum products; environmental protection and resource waste. In the traditional prebaked anode production process, a large amount of asphalt is used, and improper treatment of waste asphalt will lead to resource waste and environmental pollution. Waste asphalt contains a large amount of harmful substances. If it is directly discharged or landfilled, it will cause pollution to soil and water resources. Therefore, technical personnel in this field provide an optimization method for reducing the power consumption of prebaked anodes and improving the adhesion of modified asphalt, thereby solving the problems raised in the above background technology. Summary of the invention
[0004] 1. Technical issues to be solved
[0005] In view of the shortcomings of the prior art, the present invention provides an optimization method for reducing the power consumption of prebaked anodes and improving the adhesion of modified asphalt, which solves the problems of insufficient asphalt adhesion performance, high production energy consumption, unstable anode quality, environmental protection and resource waste in the traditional prebaked anode production process.
[0006] (II) Technical solution
[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions: an optimization method for reducing the power consumption of prebaked anodes and improving the adhesion of modified asphalt, comprising:
[0008] Optimize the asphalt modification process, adopt catalytic modification technology, add an appropriate amount of catalyst to the asphalt, improve the bonding performance and thermal stability of the asphalt, control the reaction temperature and time of the modified asphalt to achieve the best bonding performance, the reaction temperature is controlled at 280℃ to 320℃, and the reaction time is controlled at 2 to 4 hours;
[0009] Reduce the baking temperature of the pre-baked anode. By optimizing the baking curve and adopting the staged heating method, the baking temperature is reduced while ensuring the quality of the anode. The specific baking curve is: from room temperature to 200°C, the heating rate is controlled at 5°C / min; from 200°C to 600°C, the heating rate is controlled at 3°C / min; from 600°C to the final baking temperature, the heating rate is controlled at 2°C / min; the baking temperature is reduced to 1100°C to 1150°C, which is about 50°C to 100°C lower than the traditional process;
[0010] Introduce new additives, add nanomaterials to asphalt to improve the bonding strength of asphalt and the conductivity of the anode. The amount of nanomaterials added is 0.1% to 0.5% of the asphalt mass;
[0011] Optimize the molding process, adopt high-pressure molding technology, improve the density and strength of the anode, add an appropriate amount of lubricant during the molding process, reduce the friction during the molding process, and improve the molding efficiency;
[0012] Recycle waste asphalt, recycle the waste asphalt generated in the production process, and reuse it in anode production through a regeneration process. The specific regeneration process is: the waste asphalt is heated and melted to remove impurities; an appropriate amount of regeneration agent is added to improve the performance of the regenerated asphalt.
[0013] Preferably, the optimized asphalt modification process comprises the following steps:
[0014] S1. Selection and addition of catalysts. In the process of asphalt modification, the selection of catalysts is crucial. Commonly used catalysts include alumina and silicate. Adding catalysts can effectively promote the cracking of heavy components in asphalt and improve the softening point and bonding performance of asphalt.
[0015] S2. Control of reaction temperature and time. The asphalt modification temperature should be controlled between 280℃ and 320℃. If the temperature is too low, the reaction rate will be slow and the bonding performance will not be significantly improved. If the temperature is too high, the asphalt may be over-crackered, affecting the bonding performance. The reaction time should be controlled between 2 and 4 hours. If the time is too short, the reaction will be incomplete. If the time is too long, the asphalt may age and affect its performance.
[0016] S3. The specific implementation steps are as follows: first, heat the asphalt to a molten state and add an appropriate amount of catalyst; second, stir the reaction at a temperature of 280°C to 320°C for 2 to 4 hours until the asphalt reaches the required bonding properties and softening point; finally, cool the modified asphalt to room temperature for use.
[0017] Preferably, the step of lowering the prebaked anode baking temperature comprises the following steps:
[0018] S1. The first stage is from room temperature to 200℃, with the heating rate controlled at 5℃ / min. This stage is mainly to remove moisture and light components in the asphalt;
[0019] S2. The second stage is from 200℃ to 600℃, and the heating rate is controlled at 3℃ / min. This stage is the curing stage of asphalt, and the temperature needs to be slowly increased to prevent asphalt cracking;
[0020] S3. The third stage, from 600℃ to the final roasting temperature, the heating rate is controlled at 2℃ / min, and the final roasting temperature is controlled at 1100℃ to 1150℃. This stage is the sintering stage of the anode. Lowering the roasting temperature can significantly reduce energy consumption. After roasting is completed, it is naturally cooled to room temperature.
[0021] Preferably, the introduction of the novel additive comprises the following steps:
[0022] S1. Addition of nanomaterials. Adding nanomaterials to asphalt can significantly improve the bonding strength of asphalt and the conductivity of the anode, including but not limited to carbon nanotubes and graphene. Carbon nanotubes have excellent mechanical properties and electrical conductivity, which can improve the bonding strength of asphalt and the conductivity of the anode. Graphene has extremely high specific surface area and electrical conductivity, which can significantly improve the bonding performance of asphalt and the conductivity of the anode.
[0023] S2. Addition amount and dispersion process. The addition amount of nanomaterials is 0.1% to 0.5% of the asphalt mass. If the addition amount is too low, the effect is not obvious; if the addition amount is too high, it may lead to increased costs and increased process difficulty. The nanomaterials should be fully mixed with the asphalt, and ultrasonic dispersion or high-speed stirring methods should be used to ensure that the nanomaterials are evenly dispersed in the asphalt.
[0024] Preferably, the optimized molding process comprises the following steps:
[0025] S1. High pressure forming technology: The high pressure forming technology can improve the density and strength of the anode, thereby increasing its service life. The forming pressure is controlled between 50 and 100 MPa, and the holding time is controlled between 5 and 10 minutes.
[0026] S2. Use of lubricant: Adding an appropriate amount of lubricant during the molding process can reduce friction during the molding process and improve molding efficiency.
[0027] Preferably, the recycling of waste asphalt comprises the following steps:
[0028] S1. Waste asphalt regeneration process, the waste asphalt generated in the production process is recycled and reused in anode production through the regeneration process. The waste asphalt is heated to a molten state to remove internal impurities. Adding an appropriate amount of styrene to the waste asphalt can improve the performance of the regenerated asphalt. The regeneration temperature is controlled between 150°C and 200°C, and the reaction time is 1 to 2 hours. The regenerated asphalt is cooled to room temperature and set aside.
[0029] (III) Beneficial effects
[0030] The present invention provides an optimization method for reducing the power consumption of prebaked anodes and improving the adhesion of modified asphalt.
[0031] It has the following beneficial effects:
[0032] 1. In the present invention, the power consumption in the production process of prebaked anodes is significantly reduced by lowering the baking temperature and optimizing the forming process.
[0033] 2. In the present invention, by modifying asphalt and introducing additives, the bonding performance of the modified asphalt is improved, and the strength and service life of the anode are enhanced.
[0034] 3. In the present invention, by adding a proper amount of regeneration agent to waste asphalt, waste asphalt is recycled, thus reducing resource waste and environmental pollution. DETAILED DESCRIPTION
[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0036] Embodiment 1:
[0037] The embodiment of the present invention provides an optimization method for reducing the power consumption of prebaked anodes and improving the adhesion of modified asphalt, comprising:
[0038] Optimize the asphalt modification process, adopt catalytic modification technology, add an appropriate amount of catalyst to the asphalt, improve the bonding performance and thermal stability of the asphalt, control the reaction temperature and time of the modified asphalt to achieve the best bonding performance, the reaction temperature is controlled at 280℃ to 320℃, and the reaction time is controlled at 2 to 4 hours;
[0039] Reduce the baking temperature of the pre-baked anode. By optimizing the baking curve and adopting the staged heating method, the baking temperature is reduced while ensuring the quality of the anode. The specific baking curve is: from room temperature to 200°C, the heating rate is controlled at 5°C / min; from 200°C to 600°C, the heating rate is controlled at 3°C / min; from 600°C to the final baking temperature, the heating rate is controlled at 2°C / min; the baking temperature is reduced to 1100°C to 1150°C, which is about 50°C to 100°C lower than the traditional process;
[0040] Introduce new additives, add nanomaterials to asphalt to improve the bonding strength of asphalt and the conductivity of the anode. The amount of nanomaterials added is 0.1% to 0.5% of the asphalt mass;
[0041] Optimize the molding process, adopt high-pressure molding technology, improve the density and strength of the anode, add an appropriate amount of lubricant during the molding process, reduce the friction during the molding process, and improve the molding efficiency;
[0042] Recycle waste asphalt, recycle the waste asphalt generated in the production process, and reuse it in anode production through a regeneration process. The specific regeneration process is: the waste asphalt is heated and melted to remove impurities; an appropriate amount of regeneration agent is added to improve the performance of the regenerated asphalt.
[0043] The optimization of asphalt modification process includes the following steps:
[0044] S1. Selection and addition of catalysts. In the process of asphalt modification, the selection of catalysts is crucial. Commonly used catalysts include alumina and silicate. Adding catalysts can effectively promote the cracking of heavy components in asphalt and improve the softening point and bonding performance of asphalt.
[0045] S2. Control of reaction temperature and time. The asphalt modification temperature should be controlled between 280℃ and 320℃. If the temperature is too low, the reaction rate will be slow and the bonding performance will not be significantly improved. If the temperature is too high, the asphalt may be over-crackered, affecting the bonding performance. The reaction time should be controlled between 2 and 4 hours. If the time is too short, the reaction will be incomplete. If the time is too long, the asphalt may age and affect its performance.
[0046] S3. The specific implementation steps are as follows: first, heat the asphalt to a molten state and add an appropriate amount of catalyst; second, stir the reaction at a temperature of 280°C to 320°C for 2 to 4 hours until the asphalt reaches the required bonding properties and softening point; finally, cool the modified asphalt to room temperature for use.
[0047] Reducing the prebaked anode baking temperature includes the following steps:
[0048] S1. The first stage is from room temperature to 200℃, with the heating rate controlled at 5℃ / min. This stage is mainly to remove moisture and light components in the asphalt;
[0049] S2. The second stage is from 200℃ to 600℃, and the heating rate is controlled at 3℃ / min. This stage is the curing stage of asphalt, and the temperature needs to be slowly increased to prevent asphalt cracking;
[0050] S3. The third stage, from 600℃ to the final roasting temperature, the heating rate is controlled at 2℃ / min, and the final roasting temperature is controlled at 1100℃ to 1150℃. This stage is the sintering stage of the anode. Lowering the roasting temperature can significantly reduce energy consumption. After roasting is completed, it is naturally cooled to room temperature.
[0051] The introduction of new additives involves the following steps:
[0052] S1. Addition of nanomaterials. Adding nanomaterials to asphalt can significantly improve the bonding strength of asphalt and the conductivity of the anode, including but not limited to carbon nanotubes and graphene. Carbon nanotubes have excellent mechanical properties and electrical conductivity, which can improve the bonding strength of asphalt and the conductivity of the anode. Graphene has extremely high specific surface area and electrical conductivity, which can significantly improve the bonding performance of asphalt and the conductivity of the anode.
[0053] S2. Addition amount and dispersion process. The addition amount of nanomaterials is 0.1% to 0.5% of the asphalt mass. If the addition amount is too low, the effect is not obvious; if the addition amount is too high, it may lead to increased costs and increased process difficulty. The nanomaterials should be fully mixed with the asphalt, and ultrasonic dispersion or high-speed stirring methods should be used to ensure that the nanomaterials are evenly dispersed in the asphalt.
[0054] The optimization of the molding process includes the following steps:
[0055] S1. High pressure forming technology: The high pressure forming technology can improve the density and strength of the anode, thereby increasing its service life. The forming pressure is controlled between 50 and 100 MPa, and the holding time is controlled between 5 and 10 minutes.
[0056] S2. Use of lubricant: Adding an appropriate amount of lubricant during the molding process can reduce friction during the molding process and improve molding efficiency.
[0057] Recycling waste asphalt includes the following steps:
[0058] S1. Waste asphalt regeneration process, the waste asphalt generated in the production process is recycled and reused in anode production through the regeneration process. The waste asphalt is heated to a molten state to remove internal impurities. Adding an appropriate amount of styrene to the waste asphalt can improve the performance of the regenerated asphalt. The regeneration temperature is controlled between 150°C and 200°C, and the reaction time is 1 to 2 hours. The regenerated asphalt is cooled to room temperature and set aside.
[0059] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. An optimization method for reducing the power consumption of prebaked anodes and improving the adhesion of modified asphalt, characterized in that: include: Optimize the asphalt modification process, adopt catalytic modification technology, add an appropriate amount of catalyst to the asphalt, improve the bonding performance and thermal stability of the asphalt, control the reaction temperature and time of the modified asphalt to achieve the best bonding performance, the reaction temperature is controlled at 280℃ to 320℃, and the reaction time is controlled at 2 to 4 hours; Reduce the baking temperature of the pre-baked anode. By optimizing the baking curve and adopting the staged heating method, the baking temperature is reduced while ensuring the quality of the anode. The specific baking curve is: from room temperature to 200°C, the heating rate is controlled at 5°C / min; from 200°C to 600°C, the heating rate is controlled at 3°C / min; from 600°C to the final baking temperature, the heating rate is controlled at 2°C / min; the baking temperature is reduced to 1100°C to 1150°C, which is about 50°C to 100°C lower than the traditional process; Introduce new additives, add nanomaterials to asphalt to improve the bonding strength of asphalt and the conductivity of the anode. The amount of nanomaterials added is 0.1% to 0.5% of the asphalt mass; Optimize the molding process, adopt high-pressure molding technology, improve the density and strength of the anode, add an appropriate amount of lubricant during the molding process, reduce the friction during the molding process, and improve the molding efficiency; Recycle waste asphalt, recycle the waste asphalt generated in the production process, and reuse it in anode production through a regeneration process. The specific regeneration process is: the waste asphalt is heated and melted to remove impurities; an appropriate amount of regeneration agent is added to improve the performance of the regenerated asphalt.
2. The optimization method for reducing the power consumption of prebaked anodes and improving the adhesion of modified asphalt according to claim 1, characterized in that: The optimized asphalt modification process comprises the following steps: S1. Selection and addition of catalysts. In the process of asphalt modification, the selection of catalysts is crucial. Commonly used catalysts include alumina and silicate. Adding catalysts can effectively promote the cracking of heavy components in asphalt and improve the softening point and bonding performance of asphalt. S2. Control of reaction temperature and time. The asphalt modification temperature should be controlled between 280℃ and 320℃. If the temperature is too low, the reaction rate will be slow and the bonding performance will not be significantly improved. If the temperature is too high, the asphalt may be over-crackered, affecting the bonding performance. The reaction time should be controlled between 2 and 4 hours. If the time is too short, the reaction will be incomplete. If the time is too long, the asphalt may age and affect its performance. S3. The specific implementation steps are as follows: first, heat the asphalt to a molten state and add an appropriate amount of catalyst; second, stir the reaction at a temperature of 280°C to 320°C for 2 to 4 hours until the asphalt reaches the required bonding properties and softening point; finally, cool the modified asphalt to room temperature for use.
3. The optimization method for reducing the power consumption of prebaked anode and improving the adhesion of modified asphalt according to claim 1, characterized in that: The method of reducing the prebaked anode baking temperature comprises the following steps: S1. The first stage is from room temperature to 200℃, with the heating rate controlled at 5℃ / min. This stage is mainly to remove moisture and light components in the asphalt; S2. The second stage is from 200℃ to 600℃, and the heating rate is controlled at 3℃ / min. This stage is the curing stage of asphalt, and the temperature needs to be slowly increased to prevent asphalt cracking; S3. The third stage, from 600℃ to the final roasting temperature, the heating rate is controlled at 2℃ / min, and the final roasting temperature is controlled at 1100℃ to 1150℃. This stage is the sintering stage of the anode. Lowering the roasting temperature can significantly reduce energy consumption. After roasting is completed, it is naturally cooled to room temperature.
4. The optimization method for reducing the power consumption of prebaked anodes and improving the adhesion of modified asphalt according to claim 1, characterized in that: The introduction of the novel additive comprises the following steps: S1. Addition of nanomaterials. Adding nanomaterials to asphalt can significantly improve the bonding strength of asphalt and the conductivity of the anode, including but not limited to carbon nanotubes and graphene. Carbon nanotubes have excellent mechanical properties and electrical conductivity, which can improve the bonding strength of asphalt and the conductivity of the anode. Graphene has extremely high specific surface area and electrical conductivity, which can significantly improve the bonding performance of asphalt and the conductivity of the anode. S2. Addition amount and dispersion process. The addition amount of nanomaterials is 0.1% to 0.5% of the asphalt mass. If the addition amount is too low, the effect is not obvious; if the addition amount is too high, it may lead to increased costs and increased process difficulty. The nanomaterials should be fully mixed with the asphalt, and ultrasonic dispersion or high-speed stirring methods should be used to ensure that the nanomaterials are evenly dispersed in the asphalt.
5. The optimization method for reducing the power consumption of prebaked anodes and improving the adhesion of modified asphalt according to claim 1, characterized in that: The optimized molding process comprises the following steps: S1. High pressure forming technology: The high pressure forming technology can improve the density and strength of the anode, thereby increasing its service life. The forming pressure is controlled between 50 and 100 MPa, and the holding time is controlled between 5 and 10 minutes. S2. Use of lubricant: Adding an appropriate amount of lubricant during the molding process can reduce friction during the molding process and improve molding efficiency.
6. The optimization method for reducing the power consumption of prebaked anodes and improving the adhesion of modified asphalt according to claim 1, characterized in that: The recycling of waste asphalt comprises the following steps: S1. Waste asphalt regeneration process, the waste asphalt generated in the production process is recycled and reused in anode production through the regeneration process. The waste asphalt is heated to a molten state to remove internal impurities. Adding an appropriate amount of styrene to the waste asphalt can improve the performance of the regenerated asphalt. The regeneration temperature is controlled between 150°C and 200°C, and the reaction time is 1 to 2 hours. The regenerated asphalt is cooled to room temperature and set aside.